Pengaruh Disiplin Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada Budiman Swalayan Pondok - Nelvira Safni; Lucy Chairoel; Lasty Yossi Hastini; Mellyna Eka Yan Fitri (Universitas Dharma Andalas, 2023)
This study aims to determine the effect of work discipline and work stress on employee performance at Budiman Swalayan Pondok. Performance is the result of work carried out by company employees. Work discipline is the attitude of respect and obedience of every employee to the regulations set by the company. While work stress is a condition where employees feel pressured at work. The object of this research was carried out at Budiman Swalayan Pondok. The population and samples used in this study were 53 people with the sampling technique using the saturated sample technique. The method used in this study is a quantitative method with data processing using the SPSS program. The data analysis technique used in this study is based on multiple linear regression analysis. The results obtained based on the partial test show that the variables of work discipline and work stress have no effect on employee performance, and the simultaneous significant test results show that work discipline and work stress together have no effect on employee performance at Budiman Swalayan Pondok. In accordance with the results of an interview with HRD Budiman Swalayan on August 30, 2022, the performance of employees at Budiman Swalayan is considered good. This is because employees carry out company rules well and a good employee recruitment process. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh disiplin kerja dan stres kerja terhadap kinerja karyawan di Budiman Swalayan Pondok. Kinerja merupakan hasil kerja yang dilaksanakan oleh karyawan perusahaan. Disiplin kerja adalah sikap hormat dan patuh setiap karyawan terhadap peraturan yang ditetapkan perusahaan. Sedangkan stres kerja adalah suatu kondisi dimana karyawan memiliki perasaan tertekan dalam bekerja. Objek penelitian ini dilaksanakan di Budiman Swalayan Pondok. Metode dalam penelitian ini adalah metode kuantitatif deskriptif. Populasi dan sampel yang digunakan sebanyak 53 orang dengan teknik pengambilan sampel menggunakan teknik sampel jenuh. Teknik analisis data menggunakan analisis regresi linier berganda dengan menggunakan program SPSS. Hasil penelitian menunjukkan tidak adanya pengaruh disiplin kerja dan stress kerja terhadap kinerja karyawan di Budiman Swalayan Padang baik secara parsial maupun simultan. Hal ini dikarenakan karyawan mematuhi aturan perusahaan serta proses perekrutan karyawan yang baik didukung dengan religius